Pendekatan Hukum terhadap Kasus Penyalahgunaan Data Pribadi oleh Pinjaman Online - Varida, Natasha; Domini, Simon; Abdi, Muhammad (Lembaga Publikasi Ilmiah Nusantara, 2024)
The misuse of personal data by online lending platforms has become a serious threat to consumer privacy and security in the digital era. This study aims to analyze the legal approaches to addressing cases of personal data misuse by online lending services in Indonesia. The method used is a normative approach by analyzing the applicable legal framework, including Law Number 27 of 2022 on Personal Data Protection, the Electronic Information and Transactions (ITE) Law, and fintech industry-related regulations. The study finds that although there is an adequate legal foundation, significant challenges remain in terms of implementation, oversight, and inter-agency coordination. Moreover, the lack of public awareness and weak law enforcement exacerbate this issue. This article proposes several solutions, such as strengthening monitoring mechanisms, improving public digital literacy, enforcing stricter legal measures, and fostering cross-sectoral collaboration to create a safer and more transparent fintech ecosystem. With these measures, it is hoped that the protection of consumers' personal data can be significantly enhanced.